Estimativa da capacidade de hospedagem de geração distribuída em redes de distribuíção via algoritmos genéticos - SOUSA, Alana Lima de (Universidade Federal do Pará, 2019)
The use of distributed generation (DG) and distributed energy sources (DER) close to the consumer centers has been gaining prominence around the world. The high penetration level of DG will shift the operation paradigm of electric energy systems, affecting power quality delivered to consumers. The active power injection from DG can cause several consequences to distribution systems, being overvoltage issue the most impacting of them. The reverse power flow from the DG units can cause voltage rise issue on distribution networks and consequently the DG shutdown. During unity power factor (pf) operation of DG, the distribution operators control overvoltage by active power curtailment. In this scenario emerges the GD hosting capacity concept, which consists of estimating the maximum power injected by GD without compromising voltage quality of the distribution system. This dissertation estimates the DG hosting capacity on MV distribution systems using genetic algorithms, considering as main limiting factor the overvoltage issue. Performance tests were performed on IEEE 33-bus and IEEE 69-bus systems.